The Role of a Catholyte in the Foliar Nutrition of Winter Wheat Plants - Alexandrova, Elena; Khramko, Galina; Alexandrov, Boris; Hadisova , Zhanati; Abubakarova, Aminat; Musaeva, Murada (KnE Life Sciences, 2021)
This study examined the content of nitrogen (N), phosphorus (P) and potassium (K) in Tanya winter wheat plants depending on the concentration of an aqueous solution of catholyte (EKhAV-K) combined with foliar fertilizing with FlorHumate. In all phases of the growing season, tillering–stooling–heading, an increase in the content of N in the leaf and stem mass by 0.04%, 0.19% and 0.07% was shown; the content of P increased by 0.04%, 0.03% and 0.05%; and that of K raised by 0.07%, 0.09% and 0.06%. A 20% aqueous solution of EKhAV-K (pH = 9.0 and ORP = –50 mV) promoted better assimilation of N, P and K from fertilizers. The ecological safety of the wheat grain was established. The accumulation of N, P2О5 and K2О in the experimental variant of the grain was 3.09%, 8.90% and 9.09%, respectively, which was more than in the control variant. Keywords: winter wheat, foliar nutrition, catholyte, role